The Representation of muslim woman identity on magazine - Alemina BR. Perangin-angin; Good Sumbayak Sitopu Lingga; Rahmadsyah Rangkuti (EduLite: Journal of English Education, Literature and Culture, 2023)
This research looks at how Muslim women negotiate their identities with their families or the society in relation to their agnostic ideology. The study was done by examining the article published on the Magdalene.co website. Sara Mills' feminist stylistics analysis approaches will be used to do text analysis. This research uses paradigm critical constructionism and use qualitative approach. The method used is Critical Discourse Analysis (CDA) from Sara Mills. This study shows that keeping one's identity secret is a conservative family circle strategy when negotiating one's identity (as an agnostic). To achieve integration between the author and his family, however, conflict is needed. Additionally, this research demonstrates that the author has yet to arrive at a conclusive identity negotiation solution. The author's family has not yet accepted and accepted his status as a writer. This research illustrates that Magdalene.co, as a medium that promotes feminism, may serve as a comfortable place for the public at large, especially women, to voice their views.